ANALYSIS OF THE USE OF LANGUAGE IN THE FIELD OF PHONOLOGY IN THE PRESIDENT'S PRIME SPEECH AT THE UN GENERAL ASSEMBLY - Ertinawati, Yuni; Rahmadhani, Siti Zharifah Dwita; Lasaufa, Salwa; Zulfiqri, Nizar Taufik (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This analysis aims to describe language errors in the field of phonology in the first speech of Indonesian President Joko Widodo at the 75th UN general session. This research uses a qualitative research design with a type of research that interprets research objects in various ways based on scientific studies. The data source in this research is a video on the official iNews YouTube channel entitled "President Jokowi's First Speech at the 75th UN General Assembly Session". Language errors are often found in written and spoken form. However, in everyday life, errors in verbal form often occur. President Joko Widodo, as we know, comes from the Javanese tribe. Therefore, this research will analyze language errors caused by pronouncing Indonesian with a Javanese accent. This research aims to describe and analyze language errors in the field of phonology in President Joko Widodo's speech at the 75th UN General Assembly. The analysis we carried out was by looking at, listening to and noting several phoneme or utterance errors in President Joko Widodo's speech which was broadcast on the YouTube channel. The results of this research found that there were several types of phonological errors in President Joko Widodo's speech, such as: 1) Addition of phonemes, 2) Changes in phonemes, 3) Omission of phonemes. The results of this study show that there are many phoneme errors in the field of phonology